Women's Perceptions of Zika Virus Prevention Recommendations in Fortaleza, Brazil. Issue 2 (November 2020) - Stolow, Jeni; Kendall, Carl; Leal Pinheiro, Francisco Marto; Campos da Rocha Feitosa, Mariana; Alves de Almeida Furtado, Kelly; Ferreira Martins, Adriano; Paz Albino dos Santos, Mayara; Ecilda Lima Ellery, Ana; Dias, Livia; de Holanda Barreto, Ivana Cristina; Moses, Lina; Castro, Arachu; et al.
As a response to the rise in microcephaly cases in 2015, Brazilian health authorities recommended a number of Zika virus (ZIKV) prevention behaviors. This study explores the contrast between the Brazilian health authorities' health promotion response to the epidemic and the context in which the epidemic unfolded. Rapid Anthropological Assessment was used to assess how women in Fortaleza, Brazil, perceive ZIKV, ZIKV prevention recommendations, and the feasibility of adhering to these recommendations. Semi-structured interviews, informational interviews, and observations were used. The ZIKV recommendations and prevention did not represent best practices in health communication and promotion and failed to achieve their goals. Prevention recommendations were delivered without actionable steps and without considering cultural, socioeconomic, or environmental contexts. It is imperative to take advantage of this interepidemic period to apply best practices in health communication, education, and promotion to ensure populations at risk have adequate awareness, information, and resources to prevent infection.